Analysis of Spatial Diversification of Economic Growth Level in Powiats of Dolnosĺaskie Voivodship; Analiza przestrzennego zroźṅicowania poziomu rozwoju gospodarczego powiatoẃ dolnosĺaskich - Elzḃieta Chadzynśka (Comparative Economic Research. Central and Eastern Europe, 2012)
Intensive economic and urban processes which take place in Polish urbanized area have a significant impact on the changes of structure of territorial units, their functional development and demographic processes. Development of individual units is dependent on many factors like the location, demographic potential and economics. In the area of one voivodship - there are powiats with a various potential of development. As a subject of research powiats in the area of the Dolnosĺaskie Voivodship are selected. Taxonomic methods were used for the classification and grouping of powiats as a spatial objects tested in the multidimensional space of characteristics. The aim of the paper is to present the spatial variation in the level of development in the light of selected factors. – – Intensywne procesy gospodarcze oraz urbanizacyjne, ktoŕe maja miejsce w polskiej przestrzeni zagospodarowanej od przeszło 20 lat, wywieraja znaczacy wpływ na podstawowe sfery działalnosći człowieka, tj. sŕodowisko, system społeczny oraz gospodarke. Pod wpływem tych procesoẃ zachodza zmiany w strukturze jednostek terytorialnych, ich rozwoju funkcjonalnym oraz demograficznym. Rozwoj́ poszczegoĺnych jednostek uwarunkowany jest wieloma czynnikami. Mozṅa tu wyroźṅicćzynniki zwiazane z lokalizacja, potencjałem ludnosćiowym i ekonomicznym. W obszarze, jakim jest wojewod́ztwo wystepuja gminy o zroźṅicowanym potencjale rozwojowym. Jako przedmiot badanẃybrano powiaty lezȧce w obszarze wojewod́ztwa dolnosĺaskiego. Zastosowano taksonomiczne metody klasyfikacji i grupowania powiatoẃ, jako obiektoẃ przestrzennych badanych w wielowymiarowej przestrzeni cech. Celem referatu jest przedstawienie przestrzennego zroźṅicowania poziomu rozwoju gospodarczego powiatoẃ dolnosĺaskich w sẃietle wybranych czynnikoẃ.
Keywords: 330